2019
DOI: 10.1001/jamapediatrics.2019.3544
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Cow’s Milk Sensitization and Food Allergy by Avoiding Supplementation With Cow’s Milk Formula at Birth

Abstract: IMPORTANCECow's milk formula (CMF) is used to supplement breastfeeding (BF) at birth without clear clinical evidence to support the practice.OBJECTIVE To determine whether avoiding supplementation with CMF at birth can decrease risks of sensitization to cow's milk protein and/or clinical food allergy, including cow's milk allergy (CMA), overall and in subgroups stratified by 25-hydroxyvitamin D (25[OH]D) levels. DESIGN, SETTING, AND PARTICIPANTSThe Atopy Induced by Breastfeeding or Cow's Milk Formula (ABC) tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 35 publications
3
90
0
2
Order By: Relevance
“…A recent RCT showed that avoiding cow's milk formula supplementation in newborns for the first 3 days of life reduce sensitization to cow's milk and food allergy (40).…”
Section: Single Allergenic Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent RCT showed that avoiding cow's milk formula supplementation in newborns for the first 3 days of life reduce sensitization to cow's milk and food allergy (40).…”
Section: Single Allergenic Foodsmentioning
confidence: 99%
“…Similarly, a Finnish cohort study (n = 6,200 infants), with a follow-up of 18-34 months, found that exposure to cow's milk (CM) proteins within the first few days of life increased the risk for CM allergy (34). In contrast, a cohort study from Israel reported that the introduction of CM proteins within the first 2 weeks of life was associated to a lower risk of CM allergy development, and introduction between 4 and 6 months of life was associated to a higher risk (40).…”
Section: Single Allergenic Foodsmentioning
confidence: 99%
“…IgE-mediated cow's milk allergy [67]. Urashima et al demonstrated that avoiding cow's milk formula for at least first 3 days of life could prevent from sensitization to cow's milk [68]. In addition, restriction of allergenic foods during pregnancy or breast-feeding is not recommended to prevent FA [69].…”
Section: Oniwaza Et Al Reported That Delayed Introduction Of Cow's Mmentioning
confidence: 99%
“…Five RCT (Table 1) met the inclusion criteria (29)(30)(31)(32)(33)(34)(35). In 1988, Lindfors and Enocksson (29) and Lindfors et al (30) randomly assigned a 216 healthy term infants to CMF feeding (n = 112) or breastfeeding (n = 104) for the first week of life since their earliest meal (at 6 h of age) and studied the incidence of atopic diseases up to 18 months of age.…”
Section: Description Of Rct Studiesmentioning
confidence: 99%